Измерения расстояний методом спектральной интерферометрии в микро- и нанометровом диапазоне - Лукин, К. А.; Мачехин, Ю. П.; Данаилов, М. Б.; Татьянко, Д. Н. (ХНУРЭ, 2010)
The paper presents results of the optical interferometry investigations with use of low-coherent optical sources beyond their coherence zone. It is shown that when the path difference of arms in Michelson interferometer exceeds the coherence length of light-emitting diode radiation, the interference pattern in spectral domain enables to perform absolute measurements of micro and nano distances due to its dependence on both time delay and relative phase of the signals. Недостаточная кратковременная стабильность частоты лазера не позволяет выполнять интерферометрические измерения микро и нано расстояний, что существенно ограничивает применение лазерных интерферометров для измерения нано расстояний.
Keywords: интерферометрические измерения; метод спектральной интерферометрии; стабильность частоты лазера